If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1 = 2r + -7 Reorder the terms: 1 = -7 + 2r Solving 1 = -7 + 2r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-2r' to each side of the equation. 1 + -2r = -7 + 2r + -2r Combine like terms: 2r + -2r = 0 1 + -2r = -7 + 0 1 + -2r = -7 Add '-1' to each side of the equation. 1 + -1 + -2r = -7 + -1 Combine like terms: 1 + -1 = 0 0 + -2r = -7 + -1 -2r = -7 + -1 Combine like terms: -7 + -1 = -8 -2r = -8 Divide each side by '-2'. r = 4 Simplifying r = 4
| (5x+2)=5 | | -15(12)= | | 4x+3=-3x-4 | | 2(r-3)=0 | | 6x+2y=18 | | 6x+4=3x+28 | | y+(-4)=9 | | 14-7(x+1)=3x-9 | | -am*am*3m= | | x=309-d | | 23y-500=73y-100 | | 3k-17=4 | | 15ab-32ab^2= | | -6p+11=2p-13 | | 2(2f+4)=4(f+2) | | 1-2(3a-5)=3(-2a+1)+8 | | 16t^2-484=0 | | 12x+8=7x+2 | | x+6=6x-66 | | 16y+2x=18 | | -7(-3x-6)=84 | | 16x+2y=18 | | 4x-5-2x= | | .5(y+6)-3=8 | | 0.3-15=0.2x-5 | | -4m+5=-2m-15 | | 2x+7=39-6x | | (4-1)m-m=(m-1)8*4 | | s=15p | | 2x+5=41-x | | 3(6x-1)-2(x+3)=8(x+1) | | 2x+8y-26=0 |